Does D&O insurance matter for stock price crash risk? Evidence from an Asian emerging market - Ming-Te Lee; Kai-Ting Nien (Journal of Capital Markets Studies (JCMS), 2019)
Purpose - The purpose of this paper is to address the opposing views of the relationship between directors' and officers' liability insurance (D&O insurance) and stock price crash risk in a major Asian emerging stock market. Design/methodology/approach - This paper finds an endogenous relationship between D&O insurance and stock price crash risk. Hence, the two-stage least squares regression analysis is used to address the endogeneity issue when the relationship is examined. Moreover, this paper further controls the quality of other corporate governance mechanisms to investigate whether D&O insurance still has an effect on stock price crash risk. Findings - The effect of D&O insurance coverage is significantly negatively related to firm-specific stock price crash risk in Taiwan. More importantly, even when the quality of other corporate governance mechanisms is controlled, the negative relationship between D&O insurance coverage and firm-specific stock price crash risk remains significant. The evidence supports that D&O insurance serves as an effective external monitoring mechanism, strengthens corporate governance, and thus reduces stock price crash risk. Originality/value Emerging Asian markets suffer a dearth of research on the relationship of D&O insurance coverage and the firm-specific stock price crash risk. Investigating the relationship in Taiwan, the present study fills the research void. The findings show that D&O insurance plays an important role in reducing stock price crash risk of Taiwanese firms even when other corporate governance mechanisms are in place.
Keywords: 330; Taiwan; Corporate governance; Emerging market; Crash risk; Directors' and officers' (D&O) insurance